KARSINOMA MEDULER TIROID DIAGNOSIS MELALUI BIOPSI ASPIRASI JARUM HALUS - Lintong, Poppy M.; Sambuaga, Maria (Jurnal Biomedik : JBM, 2010)
Abstract: Medullary carcinoma of the thyroid is a rare thyroid cancer that is derived from parafollicular cells (C cells) of the thyroid gland. It only accounts for approximately 5% of all thyroid neoplasms. We reported a case of medullary carcinoma of the thyroid in a 44-year-old woman with tetraparesis, hypokalemia, and diarrhea. She also had two lumps in the anterior and left part of her neck. Medullary carcinoma was diagnosed by using fine needle aspiration biopsy (FNAB) of both lumps. The smears showed rich cellularity of variated cells from small and large round cells, spindles, and with plasmacitoid and hyperchromatic nuclei. These cells were dispersed and clustered. The background of the amyloid mass (amorphous material) showed as magenta masses with an MGG stain and orange masses with a Pap’s stain. The amyloid material is one of the diagnostic features of medullary carcinoma of the thyroid. The diagnosis can be confirmed with the patient’s blood calcitonin serum. In this case, we already performed an immunocytochemical stain of calcitonin but it was negative. Altough the calcitonin stain was negative, this medullary carcinoma of the thyroid could not be excluded because the patient still showed clinical symptoms due to hypercalcitoninemia. Some studies reported that the immunoreactive reaction of the calcitonin were more than 25% of the tumor cells. Keywords: medullary carcinoma thyroid, amyloid, fine needle aspiration biopsy.  Abstrak: Karsinoma meduler tiroid adalah keganasan kelenjar tiroid yang berasal dari sel-sel parafolikuler (sel C) kelenjar tiroid. Tumor jenis ini jarang ditemukan, hanya sekitar 5 % dari semua kanker tiroid. Kami melaporkan kasus seorang wanita berusia 44 tahun dengan gejala klinis tetraparesa, hipokalemia, diare, dan disertai adanya dua benjolan sebesar bola pingpong pada leher bagian anterior dan lateral kiri. Diagnosis karsinoma meduler tiroid ditegakkan melalui pemeriksaan biopsi aspirasi jarum halus pada kedua benjolan tersebut. Hasil pemeriksaan menunjukkan hapusan seluler terdiri dari sel-sel yang bervariasi: berbentuk bulat dengan ukuran kecil dan besar, spindel, dan plasmasitoid; inti  sel tampak hiperkromatik, tersebar atau berkelompok. Latar belakang terlihat bahan amorf amiloid berwarna merah magenta pada pengecatan MGG, dan berwarna jingga pada pengecatan Papanicolaou. Bahan amiloid merupakan salah satu tanda diagnostik untuk karsinoma meduler tiroid. Untuk kepastian diagnosis dapat dikonfirmasi dengan pemeriksaan kadar kalsitonin serum. Pada kasus ini  pemeriksaan imunositokimia untuk kalsitonin memberi hasil negatif, namun belum dapat menyingkirkan diagnosis karsinoma meduler tiroid.  Beberapa peneliti melaporkan imunoreaktif kalsitonin untuk karsinoma meduler tiroid 25% atau lebih pada sel-sel tumor tersebut. Kata kunci: karsinoma meduler tiroid, amiloid, biopsi aspirasi jarum halus.